AB1218-HPR Fatigue-Related Communication in Rheumatic Diseases: The Patient Perspective. (9th June 2015) - Bode, C.; Cordesmeyer, C.; Klooster, P.T.
Abstract : Background: Severe fatigue is prevalent in patients with rheumatic diseases and has significant impact on patients "quality of life". However, qualitative studies revealed that fatigue symptoms remain undiscussed in the consultations with health professionals. Objectives: Aim of this study was to describe the perceived importance of, satisfaction with and efficacy in fatigue-related communication with rheumatologists and rheumatology nurses from the perspective of the patient and to relate these perceptions to disease characteristics such as severity of fatigue, physical functioning and psychological distress. Methods: 127 patients (88% female, mean age=64 years) with a rheumatic disease filled out an online survey consisting of a fatigue-specific version of the PEPPI-5, MAF, HAQII, HADS and items on importance, satisfaction and experienced roles in fatigue-related communication. Data were analyzed with correlational and hierarchical regression analyses. Results: Only 10% of patients evaluated fatigue-related communication as (rather) not important, 45% were satisfied with the actual communication and 77% reported that the patient had to take the initiative for fatigue-related communication. Mean score on perceived efficacy regarding fatigue-related communication (16.15, SD=4.25) was lower than those in previous studies on perceived self-efficacy in communication in general. Multivariate analyses revealed depressive symptoms as the main correlate of perceived efficacy in fatigue-related communication. Conclusions: Fatigue-related communication emerged as an important topic from the patient perspective. However, satisfaction with and perceived self-efficacy in fatigue-related communication are lower compared to general patient-physician communication in chronic diseases. Possible explanations for this difference will be discussed. References: ten Klooster, P. M., Oostveen, J. C., Zandbelt, L. C., Taal, E., Drossaert, C. H., Harmsen, E. J., et al. (2012). Further Validation of the 5-Item Perceived Efficacy in Patient-Physician Interactions (PEPPI-5) Scale in Patients With Osteoarthritis. Journal of Patient Education and Counseling, 125-130. Disclosure of Interest: None declared